2014
DOI: 10.1016/j.fbr.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and fungal pathogenesis

Abstract: The gateway to the secretory pathway is the endoplasmic reticulum (ER), an organelle that is responsible for the accurate folding, post-translational modification and final assembly of up to a third of the cellular proteome. When secretion levels are high, errors in protein biogenesis can lead to the accumulation of abnormally folded proteins, which threaten ER homeostasis. The unfolded protein response (UPR) is an adaptive signaling pathway that counters a buildup in misfolded and unfolded proteins by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 59 publications
(90 reference statements)
0
31
0
Order By: Relevance
“…Endoplasmic reticulum (ER) is the gateway for the secretory pathway and is the center for post-translational modification, accurate folding, and assembly of up to 30% of the cellular proteome (Schwarz and Blower, 2016). Fungi are organisms specialized for secretion and the utilization of this mechanism is entwined to the ability to sense environmental stress, thus leading to adequate responses (Krishnan and Askew, 2014). As homeostasis in the ER secretory capacity is followed by UPR activation, and current research has reported that the UPR genes are important vulnerability points to be exploited in fungal therapy, we decided to address the scope of hacA in the dermatophyte T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endoplasmic reticulum (ER) is the gateway for the secretory pathway and is the center for post-translational modification, accurate folding, and assembly of up to 30% of the cellular proteome (Schwarz and Blower, 2016). Fungi are organisms specialized for secretion and the utilization of this mechanism is entwined to the ability to sense environmental stress, thus leading to adequate responses (Krishnan and Askew, 2014). As homeostasis in the ER secretory capacity is followed by UPR activation, and current research has reported that the UPR genes are important vulnerability points to be exploited in fungal therapy, we decided to address the scope of hacA in the dermatophyte T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) represents the gateway of the secretory pathway, where most of the plasma membrane and secreted proteins undergo proper folding and posttranslation modifications (Schwarz and Blower, 2016). The secretory system is used by different pathogens to express virulence factors, and to cope with stress conditions, which ultimately might favor their adaptation to specific biological niches (Krishnan and Askew, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies strongly implicate UPR as a central regulator of fungal pathogenesis (26). The basic features of the Hac1-dependent UPR signaling pathway appear to be well conserved in most fungal species, although several recent reports have revealed unexpected variations, such as the lack of the Hac1 homolog in the fission yeast Schizosaccharomyces pombe (27) and the absence of the canonical Ire1-Hac1 UPR in Candida glabrata (28).…”
Section: Discussionmentioning
confidence: 99%